2004
DOI: 10.1016/s1472-6483(10)60513-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial to compare the effect of recombinant human FSH (follitropin alfa) with or without recombinant human LH in women undergoing assisted reproduction treatment

Abstract: Women undergoing intracytoplasmic sperm injection (ICSI) for male factor infertility were randomly assigned to receive ovarian stimulation in a long agonist protocol with a combination of recombinant human FSH (r-hFSH; Gonal-F) and recombinant human LH (r-hLH; Luveris) (n = 212) starting on day 6 of FSH stimulation until human chorionic gonadotrophin (HCG) at a daily fixed dose of 150 IU r-hLH, or with r-hFSH alone (n = 219). There was no significant difference in the number of metaphase II oocytes retrieved (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 44 publications
1
87
1
3
Order By: Relevance
“…Four trials fulfilled the inclusion criteria [2,[8][9][10]. In 3 trials, the pituitary down-regulation with GnRH-a started in the mid-luteal phase of the preceding cycle and in 1 trial in the beginning of the menstrual cycle.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four trials fulfilled the inclusion criteria [2,[8][9][10]. In 3 trials, the pituitary down-regulation with GnRH-a started in the mid-luteal phase of the preceding cycle and in 1 trial in the beginning of the menstrual cycle.…”
Section: Search Resultsmentioning
confidence: 99%
“…Marrs et al [9] The study included (n = 431) normoovulatory women aged 18-40 with serum/plasma FSH ≤ 11.2 mIU/ml; presence of both ovaries; male partner with a diagnosis of male factor infertility; and a requirement for ICSI. Exclusion criteria included: clinically significant systemic disease; smoking more than 10 cigarettes per day; any contraindication to pregnancy; serum/plasma LH:FSH ratio >2; and more than two previous ICSI cycles in which gonadotrophin stimulation was used.…”
Section: Search Resultsmentioning
confidence: 99%
“…Marrs et al and Humaidin et al reported that rLH supplementation seems to benefit treatment outcome for women above 35 years of age (27,28). While use of LH appears beneficial in patients with lowbasal LH levels or in the late follicular phase of COS, appropriate dosages remain under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of ICSI patients with major indications for ART such as tubal infertility or unexplained infertility and/ or partners with semen abnormalities. Average patient age was 33 years (range [31][32][33][34][35][36][37][38][39][40][41][42]. All patients were with regular menstrual cycles of 25-32 days, presumed to be ovulatory.…”
Section: Patientsmentioning
confidence: 99%
“…However, in women above 35 years of age, poor responders, or with more severe pituitary GnRH-a suppression, stimulation with r-LH in the mid/late-follicular phase could be associated with improved results [6,12,24,34,37,40,41,47]. In a recent meta-analysis study it has been suggested that the supplementation with r-LH in patients of advanced reproductive age stimulated with r-FSH, may improve implantation and clinical pregnancy without affecting metaphase II (Met II) yield [31].…”
Section: Introductionmentioning
confidence: 99%